Extending Telecommunications beyond the Market : Toward Universal Service in Competitive Environments - Wellenius, Bjorn (World Bank, Washington, DC, 2012)
Competitive markets go a long way toward making telecommunications services available throughout the population. But governments often seek to extend access to services beyond what the private sector will provide on its own. To widen access, governments must remove obstacles that prevent the market from working well, and must let users decide what they need and can afford. Market mechanisms must be allowed to determine who will extend service beyond the market, how much will be invested, and where. As governments adopt such measures, they must make some critical decisions: Which services to extend? To what population groups? At what cost? Who should provide the additional service? Who should pay? The answers vary widely among countries and over time. This Note outlines options and best practices, emphasizing those relevant to emerging economies.